2017
DOI: 10.3126/jngmc.v15i1.23560
|View full text |Cite
|
Sign up to set email alerts
|

Prescribing Pattern of Antimicrobial Agents in Neonates at Nepalgunj Medical College, Kohalpur, Banke, Nepal

Abstract: Introduction: Neonates are most vulnerable to infections due to poor immune system leading to high morbidity and mortality, which justifies early diagnosis and prompt treatment with antibiotics. Antibiotics are the most frequently used drugs in Neonatal Intensive care units. Aim and Objective: The objective of present study was to identify the pattern of use of antimicrobial agents in neonates at the neonatal intensive care unit (NICU) of NGMC. Materials and Methods: A hospital-based, retrospective study (pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
3
1
0
Order By: Relevance
“…Our study documents a high prescription rate of antibiotics in neonates particularly from the Watch category. Concordant to our study high antibiotic prescription has been reported from countries like Rwanda (88%), 11 Nepal (96%) 12 and Zimbabwe (98%). 13 However, a relatively low prescription rate has also been reported from India (71% in teaching hospital) 14 and Iran (72%).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our study documents a high prescription rate of antibiotics in neonates particularly from the Watch category. Concordant to our study high antibiotic prescription has been reported from countries like Rwanda (88%), 11 Nepal (96%) 12 and Zimbabwe (98%). 13 However, a relatively low prescription rate has also been reported from India (71% in teaching hospital) 14 and Iran (72%).…”
Section: Discussionsupporting
confidence: 91%
“… 20 Meropenem prescription in our study was two times higher compared to 9% in a study from China 21 and many folds higher than a study from USA 22 (0.7%). Vancomycin use in our study was comparable to study 22.7% 12 from Nepal but higher than study from Iran – 12%. 15 These variations could be due to difference in study population, common pathogens isolated from the neonatal units, their antibiotic sensitivity patterns and number of sick neonates referred from secondary care hospitals.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations